Racial/Ethnic Differences in Prenatal Supplement and Medication Use in Low-Risk Pregnant Women - Vafai, Yassaman; Yeung, Edwina H.; Sundaram, Rajeshwari; Smarr, Melissa M.; Gerlanc, Nicole; Grobman, William A.; Skupski, Daniel; Chien, Edward K.; Hinkle, Stefanie N.; Newman, Roger B.; Wing, Deborah A.; Ranzini, Angela C.; Sciscione, Anthony; Grewal, Jagteshwar; Zhang, Cuilin; Grantz, Katherine L. (American Journal of Perinatology, 2020)
Objective This study aimed to describe the overall quantity and type of supplements and medications used during pregnancy in a low-risk cohort and to examine any racial/ethnic differences in intake.Study Design We used data from 2,164 racially/ethnically diverse, nonobese, and low-risk pregnant women participating without pre-pregnancy chronic conditions in a prospective cohort study at 12 sites across the United States. Medication data were self-reported as free text in enrollment, follow-up visit questionnaires, and abstracted from medical records at delivery. Supplements and medications data were mapped to their active ingredients and categorized into corresponding classes using the Slone Drug Dictionary. The total number and classes of supplements and medications consumed during pregnancy were calculated. Modified Poisson regression models were used to estimate the racial/ethnic differences in supplements and medications intake. All models were adjusted for maternal sociodemographic factors and study site.Results 98% of women took at least one supplement during pregnancy, with prenatal vitamins/multivitamins being most common. While only 31% reported taking no medications during pregnancy, 23% took one, 18% took two, and 28% took three or more. The percentage of women taking at least one medication during pregnancy was highest among non-Hispanic white women and lowest among Asians (84 vs. 55%, p < 0.001). All racial/ethnic groups reported taking the same top four medication classes including central nervous system agents, gastrointestinal drugs, anti-infective agents, and antihistamines. Compared with non-Hispanic white women, Hispanic (adjusted relative risk [aRR]: 0.84, 95% confidence interval [CI]: 0.71–0.98), and Asian women (aRR: 0.83, 95% CI: 0.70–0.98) were less likely to take central nervous system agents, as well as gastrointestinal drugs (Hispanics aRR: 0.79, 95% CI: 0.66–0.94; Asians aRR = 0.75, 95% CI: 0.63–0.90), and antihistamines (Hispanics aRR: 0.65, 95% CI: 0.47–0.92).Conclusion Supplement intake was nearly universal. Medication use was also common among this low-risk pregnancy cohort and differed by race/ethnicity.ClinicalTrials.gov Identifier NCT00912132.Key Points
Keywords: pregnancy; medication intake; vitamins; medication classes; medication prevalence